Between silence and noise: the amnesty in the Constituent Assembly of 1987/88 - Souza, Mayara Paiva (2018)
This text aims at analyzing the debates on amnesty and the uses of past in the Brazilian Constituent Assembly (1987/88) set up after the Military Dictatorship (1964-1985). The debates have elucidated that the past was negotiated, reinterpreted and propagated during a process of political transition which sought to lead the country out of a discretionary regime and into a consolidation of a democratic era. Between the remembrance and the forgetfulness – by means of constant negotiations around amnesty –, the game stands forward and the political strategy to men who were involved in the rise of a new regime in the country. Hence, the dictatorial past was negotiated as from political and memorial clashes established during the context of transition which culminated in the plenary of the Constituent Assembly. By the debates risen over amnesty as well as the analysis of the Journals, Annals, magazines and memorialistic works of the Constituent Assembly the magazines and memorialistic, this text is highly committed, therefore, to assess the strategies, the negotiations and, also, the interpretation about the past in this period. In addition, this work is concerned with investigating the uses of the past in the matter of the political clashes, silences and noises which together have left their marks, scars and unsolved questions. Otherwise stated, this work can be taken as a complex interlocution settled down between the memory and history realms.